Christ's Love as The Foundation for Christian Religious Education for Children with Special Needs Based on Colossians 3:12 - Wungo, Jefrianus; Mulyani, Sri; Manggi, Nelci Oktavianti (Scriptura Indonesia, 2026)
Every human being is created uniquely with strengths and limitations that demonstrate God's greatness. However, children with special needs (ABK) often face discrimination and a lack of adequate educational opportunities. In this context, Christian Religious Education (PAK) plays a crucial role in instilling the value of Christ's love as the foundation for character and spiritual development in children. This study uses a qualitative approach through literature review to explore the application of Christ's love in inclusive education. Based on Colossians 3:12, which form the foundation of Christian educators' ministry: compassion, kindness, humility, gentleness, and patience. These values encourage teachers to create a friendly, accepting, and respectful learning environment. Teachers also act as facilitators, motivators, mediators, and advocates of inclusivity in supporting the development of children with special needs. SIR, which is based on Christ's love, affirms that every child is precious before God and has the same right to develop according to His given potential. Thus, the application of Christ's love in education is a concrete manifestation of faith that works through love and forms the basis for the creation of a just, inclusive, and compassionate learning environment.